Selection of a Four Wheel Passenger Car using AHP and TOPSIS approach - Indian Scenario - S.Ravi Babu, V.Manoj, (International Journal of Advanced Science and Technology, 2020)
As there are so many models of passenger cars available in the market, common men especially middle income group people will be in dilemma while choosing the type of model of a car to be purchased. Generally car manufactures, manufacture the car by targeting the people of various income groups. In the present study, it is taken the passenger cars with the price of less than 5 lakh rupees by taking the interest of the middle income group. Parameters like Price of the car (INR), Fuel economy (Kmpl), cubic capacity (CC), seating capacity, maximum torque (Nm), Maximum power (HP), Top speed (Kmph), Fuel tank capacity (litres) are taken for the analysis in the selection of car. Models like Alto, KWID, S-Presso, Wagon-R, Triber, Tiago, Eeco, Santro, Celario, IGNIS among various companies like MARUTHI, RENAULT, TATA and HYUNDAI are taken for choosing the best possible car using AHP (Analytic Hierarchic Process) and TOPSIS techniques which are the methods of decision making of multiple criterions. With these techniques it is selected that, RENAULT KWID as the best option and RENAULT TRIBER as the least option and this selection process will be very useful for the customer in choosing the best possible option among the available ones.